CSD Communications of the Cambridge Structural Database - Gregory M. Ferrence; Clare A. Tovee; Stephen J.W. Holgate; Natalie T. Johnson; Matthew P. Lightfoot; Kamila L. Nowakowska-Orzechowska; Suzanna C. Ward (IUCrJ, 2023)
The Cambridge Structural Database (CSD) is a collection of over one million experimental three-dimensional structures obtained through crystallographic analyses. These structures are determined by crystallographers worldwide and undergo curation and enhancement by scientists at the Cambridge Crystallographic Data Centre (CCDC) prior to their addition to the database. Though the CSD is substantial and contains widespread chemical diversity across organic and metal–organic compounds, it is estimated that a significant proportion of crystal structures determined are not published or shared through the peer-reviewed journal mechanism. To help overcome this, scientists can publish structures directly through the database as CSD Communications and these structural datasets are made publicly available alongside structures associated with scientific articles. CSD Communications contribute to the collective crystallographic knowledge as nearly two thirds are novel structures that are not otherwise available in the scientific literature. The primary benefits of sharing data through CSD Communications include the long-term preservation of scientific data, the strengthening of a widely data-mined world repository (the CSD), and the opportunity for scientists to receive recognition for their work through a formal and citable data publication. All CSD Communications are assigned unique digital object identifiers (DOIs). Contributions as CSD Communications currently comprise about 3.89% of the total CSD entries. Each individual CSD Communication is free to view and retrieve from the CCDC website.